Effect of Er2O3 on structural, mechanical, and optical properties of Al2O3-Na2O-B2O3-SiO2 glass - Aktas, Bulent; Yalcin, Serife; Albaskara, Mehmet; Aytar, Emine; Ceyhan, Gokhan; Turhan, Zeynep Şilan (Journal of non-crystalline solids, 2022)
•BS glasses containing Er2O3 in varying amounts (0.5, 1, 3, and 5 mol%) were produced by the melt-quenching method.•Er3+ contributed to the network structure of the glass by connecting to oxygen atoms in the structure.•Er2O3 shifted to red the emission and excitation bands of BS glass and emerged more intense stimulation peaks with the increase in the amount of Er2O3.•Er2O3 enhanced the shear, bulk, and elasticity modulus of BS glasses.•Er2O3 improved the hardness and fracture toughness of the BS glasses. The present study aims to investigate the role of Er2O3 doping on the structural, physical, and mechanical properties of borosilicate glasses, which have Al2O3-Na2O-B2O3-SiO2 chemical composition. (100-x)[79.5SiO2–13B2O3–5Na2O–2.5Al2O3] borosilicate glasses (BS) containing xEr2O3 in varying amounts (x = 0, 0.5, 1, 3, and 5 mol%) were produced by the melt-quenching method. Structural, luminescence, and mechanical properties of Er2O3-doped BS glasses were investigated using an optical microscope, X-ray diffraction (XRD), FT-IR, luminescence spectroscopy, and Vickers microhardness tester, respectively. Furthermore, the molecular model of Er2O3-doped BS glass was drawn in the GaussView program, and the theoretical calculation of this glass was performed in the gas phase at ground state using the Hartree-Fock (HF) / LANL2DZ basis set in the Gaussian 09W program. The total electronic energy of this glass structure and the difference between the HOMO-LUMO energy levels of the glass composition (∆E) were calculated as -150893.9 Hartree, and 3.14 eV, respectively. XRD results showed that all Er2O3-doped BS glasses had an amorphous glassy structure. According to the luminescence results, the wavelength of the emission and excitation bands shifted to red with the increase in the amount of Er2O3 and emerged more intense stimulation peaks. The density, bulk, elastic, and shear modulus of BS glasses enhanced with Er2O3 addition due to the increasing bridging oxygen number in the glass network structure. Furthermore, the hardness and fracture toughness of BS glasses were enhanced with the addition of Er2O3 since the Er2O3 caused the depolymerization in the network structure of the BS glass. The results indicated that Er2O3-doped BS glasses had higher mechanical and optical properties than BS glass. Hence, these glasses may use in many applications such as radiation shielding and the field of photonics.